Ultra-fast development of Ar 2p1−10 relative densities in nanosecond-pulsed barrier discharge in argon. (1st April 2023) - Kusýn, L; Prokop, D; Navrátil, Z; Hoder, T
Abstract: A time-correlated single photon counting based optical emission spectroscopy technique is applied for an investigation of the nanosecond-pulsed barrier discharge in atmospheric pressure argon gas. We record the development of the light intensities originating from all ten Ar 2p 1 − 10 (Paschen notation) radiative states with high spatio-temporal resolution. We identify different stages of the discharge development: an early rapid electron avalanching, streamer propagation phase, generation of discharge channel and surface streamer propagation over the dielectric surface. The quantified relative 2p 1 − 10 densities for identified discharge phases enable a well-resolved insight into the ultra-fast discharge kinetics and open a possibility for the development of future detailed diagnostics of the rapidly ionized argon plasmas. Moreover, the electrical characterization of the discharge is made using the simplest equivalent circuit and it reveals new findings for the application of such an approach for similar discharges.